Penerapan Media Visual dan Audio dalam Meningkatkan Kemampuan Bahasa Anak Usia Dini yang Mengalami Speech Delay - Selvina Armiah; Yunita Yunita; Kholidah Nur (Inovasi Pendidikan dan Anak Usia Dini, 2025)
Speech delays are a developmental challenge often experienced by young children, which can affect their communication skills and social aspects. This research aims to explore the effectiveness of applying visual and audio media in improving the language skills of young children who experience speech delays. The visual media used are picture flashcards, interactive videos and picture story books, while the audio media is children's music, voice recordings and regional songs. This research was conducted at a language therapy center in Indonesia with a case study approach on 10 children aged 3–5 years. The research results show that the combination of visual and audio media can significantly increase children's attention, vocabulary understanding and speaking abilities. The use of local culture-based media such as regional songs also has a positive impact by creating a sense of relevance and emotional closeness. In addition, active involvement of parents in this process increases the success of the intervention. This research recommends consistent application of visual and audio media as part of local context-based therapy to support the language development of children with speech delays.